Rekonstruksi Kedudukan dan Fungsi Inspektorat Daerah Menuju Good Governance - Sugianto, Bambang; Utami, Iftitah (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
An autonomous regional government must necessarily have an independent and uninterruptible internal supervisory body, in order to a ggod governace government as mandated by Act No. 23 of 2014, which is accountability, transparency, effectiveness and transparency. This research aims to find out the position and function of the internal supervisory agency of the Regional Inspectorate. In discussions using an institutional reconstruction approach to the regulations of the laws governing the Regional Inspectorate. As for the obstacles, some things are institutional relations, supervisory officers and officers who are killed are appointed by the head of the district and they are accountable to the governor or the mayor. Of the District Inspectorate is the same district official as the supervised official, of the same structural office as the second esellon officer appointed by the head of the district, from the aspect of the authority of the District inspectorate not followed with sanctions so that the supervision is ineffective. For effective supervision, the District Inspectorate must be reconstructed or rearranged legally by changing the regulations of the separate legislation governing the internal supervisory agency, i.e. the District inspectorate, either by law or government regulation